A case of pulmonary veno-occlusive disease respondong to treatment with azathioprine. Issue 2 (April 1977) - Sanderson, J E; Spiro, S G; Hendry, A T; Turner-Warwick, M
Abstract : Histological features of a lung biopsy specimen from a 46-year-old woman showed all the characteristics described in veno-occlusive disease. The clinical features, however, were distinctive in that in addition to the lung involvement there was alopecia, digital vasculitic ulcers, Raynaud's phenomenon, polyarthritis, and muscle weakness. Treatment with azathioprine resulted in a progressive improvement in her condition. It is suggested that pulmonary small vein occlusion may occur as a pattern of tissue response in more than one situation and that is sometimes more amenable to therapy than has been previously reported.